(untitled) (The Review of Diabetic Studies, 2024)
Background: The management of complex chronic diseases like metastatic cancer and systemic autoimmune conditions relies on the dynamic interplay between laboratory-derived biomarkers and radiological imaging. This interdependent relationship forms a critical diagnostic and therapeutic feedback loop that guides clinical decision-making. Aim: This narrative review aims to synthesize evidence on the integrated use of serological biomarkers and medical imaging in the Internal Medicine-led management of oncology and autoimmune diseases, focusing on the systemic coordination required for effective monitoring. Methods: A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, and CINAHL (2010-2024), incorporating clinical, technological, and health services research perspectives. Results: The review identifies that optimal disease management depends on the temporal synchronization and interpretive synthesis of biomarker and imaging data. Successful integration is hampered by information silos, asynchronous testing schedules, and fragmented coordination. The implementation of unified data dashboards and the strategic deployment of health assistants for logistical coordination significantly enhance the functionality of this diagnostic loop. Conclusion: The biomarker-imaging feedback loop is a cornerstone of modern chronic disease management. Its effectiveness requires deliberate system-level integration, including technological interoperability and redesigned care coordination roles.